Структура населения беспозвоночных на поверхности почвы в условиях лесостепных ландшафтов Воронежской области - Скуфьин, К.В. (Вестник зоологии, 1968)
The article deals with the general preliminary results (determination is made up to a family) of the methodical collections of the at-soil (herpetobium) mesofauna by ground traps in various forest and open biotopes of Voronezh region in the southern part of forest-steppe. All the representatives of herpetobium fauna were taken into consideration with the body dimensions from 1 mm to 6-7 cm including small vertebrates. 26 orders are registrated with the predominance of Coleoptera, Collembola, Diptera, Hymenoptera (Formicidae and Myrmitidae), Arachnidae, Marina. Homoptera, Hemiptera-Heteroptera, Lepidoptera (caterpillars), Dermatoptera, Blattoidea, Myriapoda (Chilopoda and Diplo-poda), Phalangina, Pulmonata and rain-worms are not so numerous. The representatives of 28 families are registrated from the order Coleoptera, 39 fa-milies from Diptera which testify to a wide range of trapping ability of ground traps, though some essential additions to the quantitative characteristics of the herpetobe can be introduced by more direct methods of calculation, in particular, the visual route cal-culation of a transect type, applied by the author. The open landscapes (field, meadow) and forest belts are distinguished as to the general abundance of herpetobium fauna, the forest landscapes and fields with thick herbage are (two—three times) less abundant. The problems are discussed of ecological structure of the herpetobe; the groups of herpetobionts, herpetophils, herpetoxens and random visitors of the herpetobe are distinguished.